2006
DOI: 10.1016/j.neuron.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural Ensemble Coding of Satiety States

Abstract: The motivation to start or terminate a meal involves the continual updating of information on current body status by central gustatory and reward systems. Previous electrophysiological and neuroimaging investigations revealed region-specific decreases in activity as the subject's state transitions from hunger to satiety. By implanting bundles of microelectrodes in the lateral hypothalamus, orbitofrontal cortex, insular cortex, and amygdala of hungry rats that voluntarily eat to satiety, we have measured the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
110
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 39 publications
10
110
1
Order By: Relevance
“…Modulation of GC responses by internal states was recently reported at a single cell level (20). By the means of intrinsic imaging, we show that visceral modulations induce a large neuronal ensemble plasticity that signals a shift in tastant hedonic value associated to behavioral shift of the stimulus hedonic value.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Modulation of GC responses by internal states was recently reported at a single cell level (20). By the means of intrinsic imaging, we show that visceral modulations induce a large neuronal ensemble plasticity that signals a shift in tastant hedonic value associated to behavioral shift of the stimulus hedonic value.…”
Section: Discussionsupporting
confidence: 53%
“…We took advantage of the unique features of the central taste system where changes in internal body states, such as satiety (20) or visceral malaise (16,19) have a direct influence on primary GC neuronal responses.…”
Section: Discussionmentioning
confidence: 99%
“…That is, in all cases, the animals ingested tastants and water and for this reason we suggest that some of the tuning changes observed in all three protocols arise from evolving differences in the subjects' internals states over the course of each test session, in part due to processes involving feeding (sucrose, salt) and satiety. In this regard it has been shown that chemicals such as insulin [30,57], opiates [31], glucose [32,57] or glucagon [33] that are released throughout the feeding cycle may differentially affect taste responses throughout the gustatory axis.…”
Section: What Are the Possible Origins Of The Observed Changes In Chementioning
confidence: 99%
“…We found that despite differences in behavioral responses in the three protocols tested, we observed similar and extensive inter-sequence variability in chemosensory GC responses. We attribute these chemical tuning changes to differences in areas of the oral cavity that are subjected to the tastants as the animals ingest or reject the tastants, and to changes in tuning properties that occur as a consequence of more central processes resulting from changes in the state of the animal [22] and to compounds that are released upon ingestion that can affect gustatory responses [30][31][32][33]57]. The experiment-wide probability of eliciting appetitive responses in each trial (solid lines) was plotted for both PRE and POST sequences (grey and black, respectively).…”
Section: What Are the Possible Origins Of The Observed Changes In Chementioning
confidence: 99%
“…22 De Araujo and Simon have found that the multimodal sensory features of foods in the mouth are encoded by neuronal ensembles within the insula, and that the activity within these ensembles is hunger/satiety dependent. 32 They have also recently shown that transgenic mice that lack the trpm5 taste receptor, and are hence unable to sense sweet taste, can still learn to prefer a sucrose-containing solution because of the post-ingestive effects of sucrose. 33 Insular lesions disrupt this phenomenon.…”
mentioning
confidence: 99%